y = 6 - n
Step-by-step explanation:
Step 1 :
Given ,
input: 1, 2, 3, 4 ,5 Output: 5, 4, 3, 2, 1
Let y = m x + c be the linear function
Step 2 :
When we take the input as 1, the output is 5, and when input is 2 the output is 4
so we have x,y as (1,5) and (2,4)
Hence substituting this in the linear function we get,
5 = m (1) + c and 4 = m (2) + c
=> m + c = 5 and 2 m + c = 4
Step 3 :
Solving for m and c with these 2 equations , we have
m = -1 and c = 6
so we have the equation as y= (-1) x + 6
When the input is n, x = n
so output is y = (-1) n + 6
y = 6 - n